Novel accessory safety footswitch permitting dual control of surgical electrical diathermy: an asset in risk management in surgical training?. Issue 4 (29th June 2020) - Eisawi, Abdalla; Aung, Myat; Canelo, Ruben
Abstract : Introduction: Human error contributes to the majority of adverse events in the operating theatre environment. Many processes exist to limit the incidence of such adverse events. However, the role of technology and device advancement has been limited in this respect. Methods: A dual-controlled accessory electrical diathermy footswitch (abortive diathermy footswitch device or ADF) concept was developed in an attempt to improve patient safety in theatre. The activation of the ADF allows a senior surgeon to control the activation of diathermy devices by a junior surgeon by deactivating diathermy devices when the ADF footswitch is operated. Results: The ADF device was constructed as a final working and tested prototype in association with the local medical engineering department at the Cumberland Infirmary in Carlisle. The device was clinically tested during two separate theatre sessions involving five elective laparoscopic cholecystectomies. Conclusions: We demonstrated the feasibility and functionality of the ADF device and propose a role in surgical training through potentially limiting surgical errors associated with the use of electrical diathermy during training and expanding accessible surgical experience.